RANCANG BANGUN SISTEM PELAYANAN KESEHATAN POSKESDES DESA TANJUNG MIRING BERBASIS WEB - Rensi Novrianti; Yuntari Purbasari; Hepnyi Samosir (Elkom: Jurnal Elektronika dan Komputer, 2024)
The design of the POSKESDES health service system for tanjung miring village was carried out so that the use of information technology was used as a tool to increase productivity for POSKESDES for tanjung miring village. The method used in this study is a qualitative descriptive method, which means carefully recording various phenomena that are seen and heard and read via interviews or field notes, photos, videos, personal documentation, notes and memos and so on. The results of this research are to help manage information about POSKESDES so that it can help the surrounding community. Can assist POSKESDES in terms of disseminating information about the latest activities and the latest information at POSKESDES in tanjung miring village and can assist in the patient service process.